The Tradition of Classicism and Sculpture of Leningrad — Saint Petersburg: The Sculpture Collection of the State Russian Museum - Slavova, Liubov’ A. (Actual Problems of Theory and History of Art, 2015)
The author traces the development of classical principles in Russian sculpture from the period of A. T. Matveev to his disciples who finished their creative activity in the 1990s. Matveev school of sculpture was based on the traditions of classicism and became a unique artistic phenomenon in the history of Soviet sculpture. It was a result of pedagogical activities of the outstanding Russian sculptor Alexander Matveev, whose oeuvre is inseparably linked to the principles of classical sculpture. Classicality as a stylistic category of Matveev’s work was noted by his contemporaries. One of the critics defined the peculiarity of the first graduates of Matveev’s school in the 1920s and 1930s as a “classicizing sculptural style” in Soviet sculpture. The images of young characters of the new Soviet epoch dressed in modern clothes invariably revealed classical ideals still retaining high artistic level. However, the politics of ideological pressure and “class approach” even in the sphere of studying and preserving sculptural traditions controlled and held the natural creative process back. Later on, until the 1960s, Matveev’s creative system was forced to oppose official culture:it was a subject to groundless criticism. The works were accused of “formalism” and non-compliance with “standards” of Soviet sculpture. The 1960s–1990s were the heyday of Matveev school. The whole galaxy of sculptors had emerged. They enjoyed their individual peculiarities, though retained Matveev’s typical way of sculptural vision and creative rethinking of classical heritage. It encouraged the artists of the Matveev circle in their quests for modern sculptural forms. The Russian Museum owns a collection of sculptural works made by several generations of artists — Alexander Matveev’s followers — shown at the Alexander Matveev and His School exhibition in 2005.